The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1177/13674935231171453
|View full text |Cite
|
Sign up to set email alerts
|

Influence of parental anxiety and beliefs about medicines on feeding and exercise in children living with asthma

Abstract: This study’s primary objective was to establish differences in beliefs about medicines, levels of asthma-related anxiety and diet and exercise behaviours between parents of children with well controlled and poorly controlled asthma. Secondary objectives were to explore how asthma control might shape relationships between parental cognitions and parenting practices concerning paediatric asthma. Parents of children with asthma aged 10–16 years ( N = 310) completed standardised questionnaires measuring beliefs ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Research has shown that parents, their characteristics and attitudes, such as higher education of the mother, the father’s smoking, or the parents’ asthma, play a significant role in the development and control of childhood asthma [ 26 , 27 ]. Parents’ attitudes towards medication and anxiety about the disease were significantly associated with asthma control, and also influenced asthma outcomes through diet and exercise habits [ 28 ]. Therefore, the extent to which either the child or the parent believes that they can influence the disease through a healthy lifestyle will also affect its outcomes [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that parents, their characteristics and attitudes, such as higher education of the mother, the father’s smoking, or the parents’ asthma, play a significant role in the development and control of childhood asthma [ 26 , 27 ]. Parents’ attitudes towards medication and anxiety about the disease were significantly associated with asthma control, and also influenced asthma outcomes through diet and exercise habits [ 28 ]. Therefore, the extent to which either the child or the parent believes that they can influence the disease through a healthy lifestyle will also affect its outcomes [ 29 ].…”
Section: Introductionmentioning
confidence: 99%